KONDISI SOSIAL IRAN PADA MASA MONGOL, TIMURIYAH, DAN SAFAWIYAH TAHUN 1295-1786 M - Muhammad Farih Fanani (Jurnal Tamaddun, 2022)
The Mongols (Ilkhan), Timurids, and Safavids were the three kingdoms in Iran. The three kingdoms played a significant role in advancing Islamic civilization. The three Islamic kingdoms were not born from Arab circles, so it is very interesting to discuss further. The Mongols invaded Islamic territory and divided Persia into Hulagu, which became the forerunner to the birth of the Ilkhan dynasty. Ilkhan's power was then continued by Timuriyah with the main character, Timur Lenk. Then power shifted to the Safavids. The Safavids then managed to become a great power by legitimizing their power with a Shia approach and Qizilbash military power. This article uses the historical method with a political sociology approach. The historical method uses four steps in historical writing to obtain a systematic and chronological description, namely heuristics, verification, interpretation, and historiography. The political sociology approach is used to see a historical event from a social and political point of view. Especially those that include the concepts of society, state, power, and social structure.